Problems of Creating Sustainable Urban Transport Systems in European and Asian Cities - Paradowska, Monika (Problemy tworzenia zrównoważonych systemów transportu miejskiego w miastach Europy i Azji, 2010)
Due to the increasing level of external costs of transport, especially noticeable in urban areas characterised by high population density and countless number of socio-economic processes, there is a great need for creating sustainable urban transport systems in cities all over the world. European and Asian cities, despite differences between them, have in common that they are facing large intensity of road transport externalities and have to develop various solutions to make transport systems sustainable. In this paper some examples of external costs of transport in European and Asian cities are presented, and some basic levels of cooperation between different administrative units and institutions connected with creating sustainable urban transport systems in Europe and Asia are outlined.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 186-196
Keywords: sustainable transport; urban transport; transport systems; positive external effects of transport; external costs of transport; European and Asian cities